Anti-inflammatory effect of amalgam on periapical lesion cells in culture - Eraković, Mile; Duka, Miloš; Bekić, Marina; Milanović, Marijana; Tomić, Sergej; Vučević, Dragana; Čolić, Miodrag (Vojnosanitetski pregled, 2021)
Background/Aim. Amalgam has been used for years in dentistry, but the controversy on its adverse effects, both on local oral/dental tissues and systemic health, still exists. When used for retrograde filling in apical surgery, amalgam comes in close contact with the periapical tissue, and it is sometimes responsible for the induction of periapical lesion (PL) or its exacerbation. Therefore, the aim of the study was to examine the effect of amalgam on cytotoxicity and production of pro-inflammatory cytokine by cells isolated from PL. Methods. Conditioned medium from freshly prepared amalgam (ACM) was performed according to the ISO 10993-12 by incubating the alloy in RPMI medium (0.2 g/mL) for 3 days at 37°C. Cells were isolated from 20 human PLs after apicoectomy by collagenase/DNA-ase digestion and cultured with different dilutions of ACM. Cytotoxicity was determined by MTT assay (n = 7 cultures) and apoptosis/necrosis assays (n = 8 cultures), whereas cytokine production was measured by a Flow Cytomix Microbeads Assay (n = 8 cultures). Results. Undiluted (100%) and 75% ACM was cytotoxic due to induction of apoptosis of PL cells. Non-cytotoxic concentrations of ACM (50% and 25%) inhibited the production of pro-inflammatory cytokines (TNF-α, IL-1β, IL-6, and IL-8), concentration-dependently. Conclusion. For the first time, our results showed an unexpected anti-inflammatory property of amalgam on PL cells, which could be beneficial for PL healing after apicoectomy.